Training and Development and Organizational Performance: The Moderating Effect of Organizational Commitment (International Journal of Scientific Research and Management (IJSRM), 2017)
The purpose of this study was to find out the impact of training and development on organizational performance and to find out the moderating effect of organizational commitment on the relationship between training and development and organizational performance. This study was carried out in three companies namely Kenya Power, KenGen and Mumias Sugar Company. Descriptive survey design was adopted in the study. The study population was all the 5866 employees in the three companies. The findings of the study were that training and development had a significant effect on organizational performance. The study further showed that affective commitment, continuance commitment and normative commitment moderated the relationship between training and development and organizational performance.